2021
DOI: 10.3389/fnins.2021.657126
|View full text |Cite
|
Sign up to set email alerts
|

Longer and Deeper Desaturations Are Associated With the Worsening of Mild Sleep Apnea: The Sleep Heart Health Study

Abstract: Study ObjectivesObesity, older age, and male sex are recognized risk factors for sleep apnea. However, it is unclear whether the severity of hypoxic burden, an essential feature of sleep apnea, is associated with the risk of sleep apnea worsening. Thus, we investigated our hypothesis that the worsening of sleep apnea is expedited in individuals with more severe desaturations.MethodsThe blood oxygen saturation (SpO2) signals of 805 Sleep Heart Health Study participants with mild sleep apnea [5 ≤ oxygen desatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Because some of the originally scored desaturation event annotations had disappeared due to known data corruption (The National Sleep Research Resource, 2021), SpO 2 signals were rescored automatically with Noxturnal software (version 5.1.19824, Nox Medical, Reykjavík, Iceland). Agreement between the automatic and manual scorings using the same methods in the same dataset has been previously presented extensively and been shown to be excellent (Karhu et al, 2021). No desaturation scoring criteria exist in the American Academy of Sleep Medicine (AASM) guidelines besides a minimum transient drop of 3% or 4% from the baseline (Berry et al, 2017).…”
Section: Psg and Spo 2 -Derived Parametersmentioning
confidence: 89%
See 2 more Smart Citations
“…Because some of the originally scored desaturation event annotations had disappeared due to known data corruption (The National Sleep Research Resource, 2021), SpO 2 signals were rescored automatically with Noxturnal software (version 5.1.19824, Nox Medical, Reykjavík, Iceland). Agreement between the automatic and manual scorings using the same methods in the same dataset has been previously presented extensively and been shown to be excellent (Karhu et al, 2021). No desaturation scoring criteria exist in the American Academy of Sleep Medicine (AASM) guidelines besides a minimum transient drop of 3% or 4% from the baseline (Berry et al, 2017).…”
Section: Psg and Spo 2 -Derived Parametersmentioning
confidence: 89%
“…Moreover, as no scoring criteria for desaturations exist in the AASM guidelines (Berry et al, 2017) besides a transient drop of 3% or 4%, the alteration of the used scoring criteria would affect the number and severity of desaturation events. However, the used scorings can be assumed to be valid, as in the exact same dataset correlations and median differences between automatic scorings and a subset of manual scorings have been shown to be excellent (Karhu et al, 2021). Furthermore, apneas and hypopneas were not automatically rescored as they were found to be insufficiently accurate without manual editing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study 58.9% of high-tech employees were found to have mild OSA. Karhu et al (2021) stated that if patients with long-term apnea do not receive treatments, their OSA would be aggravated by prolonged exposure to deoxygenation saturation concentration. A study on the natural evolution of apnea found that even if there is no increase in BMI, patients with mild to moderate OSA tended to develop severe OSA after an average of 17 months (Pendlebury et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, other configurations may lead to different results. On the other hand, we included Nadir SpO2 in our analyses because it has been observed that the depth of desaturations is associated with increased OSA-related negative consequences in adults (Kulkas et al, 2013;Karhu et al, 2021). However, it would be an interesting future goal to assess other oximetric variables such as oxygen desaturation index or hypoxic burden.…”
Section: Other Limitations and Future Stepsmentioning
confidence: 99%